Serum endothelin-1 and transforming growth factor-? levels in the newborns with respiratory distress - Benzer, Derya; Aygun, A. Denizmen; Godekmerdan, Ahmet; Kurt, A. Nese (Citak); Akarsu, Saadet; Yilmaz, Erdal (Hindawi Ltd, 2006)
The purpose of this present study was to evaluate the serum levels of ET-1 and TGF-beta in the newborns with respiratory distress. In this study, newborns with respiratory distress hospitalized into the Newborn Intensive Care Unit were included. The highest values of ET-1 and TGF-beta were obtained from newborns with diagnosis as meconium aspiration syndrome (5.70 +/- 5.87 pg/mL and 3.75 +/- 1.94 pg/mL, resp) in the sample obtained in the first six hours after birth, and these are statistically different from control group ( P <.05). Also, same results were obtained for newborns with respiratory distress syndrome (3.37 +/- 1.59 pg/mL and 2.05 +/- 0.98 pg/mL, resp). After oxygen treatment, ET-1 values obtained in the first six hours of life were decreased regularly in the following days ( P <.05). In the differentiating diagnosis of the respiratory distress of newborns, the investigation of ET-1 and TGF-beta levels is meaningful. The ET-1 levels investigated in the first six hours is more useful in determining the prognosis, and repeating ET-1 levels in the following days is more meaningful to determine clinical response.
Keywords: Chronic Lung-Disease; Pulmonary-Hypertension; Plasma Endothelin-1; Preterm Infants; Mechanisms; Increase; Fluid